“Hoy no, pero mañana si” Estudio correlacional entre los rasgos de Personalidad y la Procrastinación Académica de las/los estudiantes de Psicología de la Universidad Antonio Nariño en la Ciudad de Bogotá D.C. (2017)
This research focuses its interest about the study of the relationship that exists between the deliberate intention to postpone irrationally the academic activities (Procrastination) and the personality characteristics of the students of the Psychology program of the Antonio Nariño University in Bogotá, DC, city. The research was developed with 62 students of the program using a non-experimental correlational type design. To measure the variable procrastination was used the Tuckman Academic Procrastination Scale validated for the Colombian context by Angarita, Sánchez and Barreiro (2010) and for the personality variable, the Personality Test 16 PF. The results obtained allowed to identify that the level of procrastination of the students tends to be low and with a marked inclination towards the indifference type, followed by the delay type. Regarding the correlation of the variables, the personality factors that showed greater strength in relation to the variable procrastination in its order are evidenced: C Emotional Stability, Q3 Self-esteem, G Perseverance, H Spontaneity, O Consciousness and Q4 Anxiety.